Quality of life, general health and anxiety in dental students with temporomandibular disorders - Vanessa Soares Souza; Francisbênia Alves Silvestre; Nicole Escórcio de Menezes; Wagner Araújo de Negreiros; Marcelo Barbosa Ramos; Karina Matthes de Freitas Pontes; Rômulo Rocha Regis; Lívia Maria Sales Pinto Fiamengui; Raniel Fernandes Peixoto (Acta Scientiarum. Health Sciences, 2024)
This study evaluated the prevalence of temporomandibular disorders (TMD) in dental students and its association with psychosocial factors (general health, quality of life and anxiety). Sixty students were initially selected and analyzed for TMD presence by the Diagnostic Criteria for TMD (DC/TMD). The participants answered self-administered questionnaires to assess general health (General Health Questionnaire – GHQ), quality of life (World Health Organization Quality of Life – WHOQOL-brief), and anxiety (State-Trait Anxiety Inventory – STAI). The prevalence of TMD among the participants was 43.33% (n = 26), 26% (n = 16) were diagnosed with painful disorders, being myalgia the most prevalent diagnosis (21.67%; n = 13). About 16.67% (n = 10) of the participants presented disc displacement with reduction. All indicators of general health showed statistically significant difference such as psychological stress (p = 0.004), death wish (p = 0.006), distrust in performance (p < 0.001), sleep disturbance (p = 0.025), psychosomatic disorder (p < 0.001), and general health (p = 0.003). Quality of life was associated with the presence of painful disorder in the physical (p = 0.001), psychological (p = 0.003) and general (p = 0.015) dimensions. The state of anxiety (STAI-S) showed statistically significant difference (p = 0.042). In conclusion, painful muscle disorder was the most prevalent TMD subtype in dental students and several psychosocial factors are important indicators of TMD presence.